Cultural relations in the global community problems and prospects - Bickley, Verner Courtenay; Philip, Puthenparampil John 1916- (Abhinav, 1981)
Outcome of a conference on "Emerging Issues in Cultural Relations in an Interdependent World", held in Honolulu, 1976.